PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP LOYALITAS KONSUMEN PADA TOKO KINTAN DI CERMEE DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Sariyanti, Sariyanti; Sari, Lita Permata; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Marketing management is an analysis of planning, implementing and controlling programs designed to create, build and maintain profitable exchanges with target markets to achieve organizational goals. The purpose of this study was to analyze and examine the effects of product and service quality on consumer loyalty through consumer satisfaction. The population in this study was consumers of Kintan Store in Cermee. The sampling technique was determined by simple random sampling method. Data analysis and hypothesis testing in this study used Partial Least Square Structural Equation Modeling (PLS-SEM). The results of direct effect hypothesis test using Smart PLS 3.0 application showed that product quality has a negative but not significant effect on consumer satisfaction, service quality has a significant positive effect on consumer satisfaction, product quality has a negative but not significant effect on consumer loyalty, service quality has a positive but not significant effect on consumer loyalty, consumer satisfaction has a significant positive effect on consumer loyalty, product quality has a negative but not significant effect on consumer loyalty through consumer satisfaction, service quality has a significant positive effect on consumer loyalty through consumer satisfaction.